DIRECTIVE ILLOCUTIONARY ACT USED IN FEEL THE BEAT MOVIE - Andari, Ni Komang Meri; Candra, Komang Dian Puspita; Putri, IGA Vina Widiadnya (Institut Pariwisata dan Bisnis Internasional, 2021)
This study presents the Directive Illocutionary act of the characters utterances found in the movie. The data was taken from the American Movie entitled Feel the Beat. The data was collected by downloading the movie and watching repeatedly and deeply to understand the content of the movie. The data was done by note down and classified based on the types of Directive Illocutionary acts. The data was presented descriptive qualitative method in which were described and interpreted in narratives form in understood the study using the theory and analyzed based on the theory about Directive Illocutionary acts that proposed by Searle (1976) and supported by theory from Yule (1996). In the analysis of selected dialogue in the movie, the result shows that there are 24 data that contained Directive Illocutionary acts are found from the movie. It can be classified into the function of Directive Illocutionary Act which were commands, orders, requests, and suggestions. The intended meaning that contain in the Directive Illocutionary acts was found in this movie supported by the context of situation that occurs in Feel the Beat movie.